2020
DOI: 10.21203/rs.3.rs-31458/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome Analyses Revealed the Ultraviolet B Irradiation and Phytohormone Gibberellins Coordinately Promoted the Accumulation of Artemisinin in Artemisia Annua L.

Abstract: Abstract Background: Artemisinin-based combination therapy has become the preferred approach for treating malaria and has successfully reduced malaria-related mortality. Currently, the main source of artemisinin is Artemisia annua L., and thus, it is of strategic importance to enhance artemisinin contents in A. annua plants. Phytohormones and illumination are known to be important external environmental factor that can h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…GAs also have a positive regulatory effect on artemisinin content and yield. Metabolome and transcriptome analysis by Ma et al ( 2020 ) revealed that GA and UV-B irradiation coordinately promoted artemisinin accumulation in A. annua by up-regulating key biosynthetic genes like ADS and CYP71AV1. Co-overexpression analysis suggested that certain selected NAC and MYB transcription factors regulated the expression of these genes to enhance artemisinin production.…”
Section: Artemisinin Enhancement Strategiesmentioning
confidence: 99%
“…GAs also have a positive regulatory effect on artemisinin content and yield. Metabolome and transcriptome analysis by Ma et al ( 2020 ) revealed that GA and UV-B irradiation coordinately promoted artemisinin accumulation in A. annua by up-regulating key biosynthetic genes like ADS and CYP71AV1. Co-overexpression analysis suggested that certain selected NAC and MYB transcription factors regulated the expression of these genes to enhance artemisinin production.…”
Section: Artemisinin Enhancement Strategiesmentioning
confidence: 99%
“…Transcriptome sequencing is currently the best technique available to analyze functional genes and gene expression patterns. In this respect, however, only small portions of Artemisia's chloroplast genome and transcriptome have been sequenced (Danova et al, 2012(Danova et al, , 2018Srivastava and Sangwan, 2012;Kim et al, 2020;Ma et al, 2020;Shahzadi et al, 2020), and only for A. annua has a draft nuclear genome sequence been fully reported (Shen et al, 2018). The advent of omics sequencing technology has promoted the rapid development of chloroplast genomics and genetics of medicinal plants, so for species whose genomic information is unavailable, highthroughput RNA sequencing and data analysis are powerful tools for mining genes with specific biological functions.…”
Section: Introductionmentioning
confidence: 99%